Acute paracoccidioidomycosis worsened by immunosuppressive therapy due to a misdiagnosis of Crohn’s disease - Falcão, Eduardo Mastrangelo Marinho (2023)
Ethics statement - The Research Ethics Committee of the Evandro Chagas National Institute of Infectious Diseases (INI/FIOCRUZ), a reference center for PCM in Rio de Janeiro State, Brazil approved this study (appreciation number 26066619.0.0000.5262), and a written formal consent was obtained from the patient.